الشاهد الشعري في القاموس المحيط للفيروز آبادي - دراسة معجمية- - زايد، آمنة; طالب، رقية (University of Eloued جامعة الوادي, 2025)
إنّ الشواهد الشعرية في القاموس المحيط تؤدي دوراً داعماً في شرح الألفاظ وتوثيقها، وهي جزء من منهجية الفيروز آبادي في التأليف المعجمي، وإن كانت محدودة من حيث الكمية، لكنها مهمة من حيث النوع والدّلالة. ولقد جاء القاموس جامعًا ومختصراً لأعمال سابقة (مثل المحكم لابن سيدة والصحاح للجوهري) وامتاز بترتيب مادته المعجمية على نظام الجوهري؛ أي الترتيب على أواخر الأصول، مما ساعد على تسهيل البحث في زمنه، كما أنه أصبح مصدرًا أساسيًا لِطُلاب اللغة العربية. The poetic evidence in Al-Qamoos Al-Muhit plays a supporting role in explaining and documenting words، and is part of Al-Fayruzabadi’s methodology in lexical composition. Although limited in quantity، it is important in terms of quality and meaning. The dictionary is a comprehensive and concise compilation of previous works (such as Al-Muhkam by Ibn Seeda and Al-Sahah by Al-Jawhari). It is distinguished by the arrangement of its lexical material according to Al-Jawhari’s system، i.e. arrangement according to the last roots، which helped facilitate research in its time. It also became a basic source for students of the Arabic language.
مذكرة .ماستر . لسانيات عامة 2025
Keywords: المعجم، القاموس، الشاهد، المدخل، الدلالة.; lexicon، dictionary، witness، introduction، significance